Evaluation of maize silage productivity (Zea mays) for bovine feed using precision agriculture - Clavijo Cabrera, Octavio
In the livestock sector, the current conditions for the production of green fodder by means of maize silage (Zea mays) are not enough profitable due to the high production costs and the low productivity established through the traditional management of the maize crop. The objective of this study is to evaluate the production per maize area, without increasing costs, applying specific principles of Site-specific Farming, through a specific agronomic management per production site and thus avoid consequences such as low income to the producer and deterioration of grienvironmental conditions of the lots.The study was carried out with apprentices of the Technologist in Ecological Agricultural Production. The study consisted in determining the content of nutrients in the soil using a statistically segmented sampling to fertilize each fraction according to the requirements of the crop; by applying the nutrients rationally in each sector of the lot, in a the necessary grade and dose for a high forage production.